2005
DOI: 10.1097/01.ccm.0000162381.24074.d7
|View full text |Cite
|
Sign up to set email alerts
|

Severe community-acquired pneumonia as a cause of severe sepsis: Data from the PROWESS study*

Abstract: CAP associated with a high Pneumonia Severity Index score, bacteremia, or an intense coagulation and inflammatory response requiring intensive care unit care were indicators of a high risk of death from severe sepsis. In patients with severe sepsis resulting from CAP, a readily identifiable disease, DrotAA, improved survival compared with placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
136
3
6

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(147 citation statements)
references
References 28 publications
2
136
3
6
Order By: Relevance
“…A re-examination of the data from that study demonstrated that a threshold CURB-65 score of o3 was associated more with a decrease in 28-day mortality in drotrecogin alpha-treated patients of 10.8% when compared with controls (p50.018) versus a decrease in mortality in treated patients in PSI classes IV and V of 9.7% compared with controls (p50.013) [11]. The CURB-65 has also been studied in patients in South Africa with bacteraemic pneumococcal pneumonia, including both HIV-seropositive and -seronegative individuals, and was found to have a similar predictive ability for mortality to the PSI, even in HIVseropositive patients with a median CD4 cell count of ,200 cells?mL -1 [12].…”
Section: # Mmentioning
confidence: 99%
“…A re-examination of the data from that study demonstrated that a threshold CURB-65 score of o3 was associated more with a decrease in 28-day mortality in drotrecogin alpha-treated patients of 10.8% when compared with controls (p50.018) versus a decrease in mortality in treated patients in PSI classes IV and V of 9.7% compared with controls (p50.013) [11]. The CURB-65 has also been studied in patients in South Africa with bacteraemic pneumococcal pneumonia, including both HIV-seropositive and -seronegative individuals, and was found to have a similar predictive ability for mortality to the PSI, even in HIVseropositive patients with a median CD4 cell count of ,200 cells?mL -1 [12].…”
Section: # Mmentioning
confidence: 99%
“…Исследование PROWESS показало биологичес кую активность активированного протеина С (дрот рекогина альфа) и его клиническую эффективность у больных с тяжелым сепсисом со статистически достоверным снижением относительного риска ле тального исхода на 19,4 % и абсолютным снижением летальности на 6,1 % [6]. При ретроспективном ана лизе пациентов с пневмонией без сепсиса различий по смертности не получено.…”
Section: возможности неантибактериальной терапии внебольничной пневмонииunclassified
“…4 Many patients included in this trial had concomitant ARDS, and many had pneumonia as the primary source of sepsis. 24 One can hypothesise that the beneficial effect of APC was the result, at least in part, of APC on intra-alveolar coagulopathy. Indeed, rh-APC exerts anticoagulant effects in the human lung challenged with endotoxin: 25 activation of coagulation after pulmonary challenge with endotoxin is inhibited and increased PAI-1 activity is diminished by infusion of rh-APC.…”
Section: Clinical Considerationsmentioning
confidence: 99%